Analisis Teknik Penerjemahan Istilah Kebudayaan dalam Kumpulan Cerita Pendek: Karma - Muliawati, Ni Wayan Pering (Kementerian Sekretariat Negara Republik Indonesia, 2020)
This study aims to identify the techniques and ideology of translation of cultural terms in the collection of short story entitled ‘Karma’. This research is started with identifying the cultural terms contained in the book ‘Karma’, then continued with analyzing the techniques of translation and the ideology that tends to be used by the translator. Two theories support this study; technique of translation theory proposed by Molinda and Albir and ideology of translation proposed by Nababan. Documentation method was used in this study by reading attentively and doing note-taking technique. The method implemented to analyze the data was qualitative method, and the result of analysis is explained descriptively. The study shows that there are 85 (eghty five) cultural terms in the book ‘Karma’. There are 10 (ten) techniques of translation have been used by the translator to translate these cultural terms: literal translation (21), borrowing (10), modulation (5), calque (3), generalization (3), reduction (2), amplification (2), variation (2) and description (2). Based on the percentage of the the techniques of translation implementation, it was found that domestication orientation was applied 60,1% (51 times) and foreignization orientation was applied 39,9% (34 times). Therefore, the ideology of Karma translation tends to be domesticating. Keywords: cultural terms, techniques of translation, ideology of translation, domestication, foreignization, Karma